POLITIK LOKAL DI KOTA BEKASI: PERAN FORUM KERUKUNAN UMAT BERAGAMA MELALUI RELASI PATRON KLIEN DENGAN BADAN KESATUAN BANGSA DAN POLITIK DALAM MENJAGA KERUKUNAN BERAGAMA TAHUN 2018-2021 - Nauffal Hilal (2022)
The purpose of this study was to find out how the role of the Religious Harmony Forum (FKUB) through patron-client relationships with the National Unity and Political Agency (Kesbangpol) in maintaining religious harmony in Bekasi City in 2018-2021. FKUB Bekasi City is a social organization formed by the government that actively carries out activities related to maintaining harmonization and harmony between religious communities in Bekasi City. The method used in this research is descriptive qualitative using primary data sources and secondary data. Data collection techniques were carried out by conducting interviews and library documentation. The results of this study indicate that FKUB has a very important role in creating religious harmony in the city of Bekasi through patron-client relationships with the Kesbangpol Agency. Bekasi City FKUB has several strategies and work programs in carrying out their main tasks and functions. The work programs include: conducting socialization, establishing and empowering the Religious People's Council (MUB), establishing interfaith Millennial Youth management, conducting work visits and comparative studies to areas that have a high level of harmony and tolerance, conducting meetings or gatherings. between religious leaders and community leaders, and by continuing to establish synergy and good relations with the Bekasi City Kesbangpol Agency. The patron-client relationship that exists between the Bekasi City FKUB and the Kesbangpol Agency can be seen from the flow of patrons to clients and the flow of clients to patrons. Keywords: religious harmony, patrons clients, local political